The Optimal Point for Fiscal Decentralization - Nguyen Viet Hanh, Viet Hanh (ĐHKT, 2016)
The paper's purpose is to shed more light on the impact of fiscal decentralization on the economy and determine whether or not a tipping point can be identified asan optimal point of fiscal decentralization. To doso, we proposed a new theoretical model to link two measurements of fiscal decentralization such as fiscal autonomy an d fiscal importance to provincial GDP.